Bilateral clinical anophthalmia associated with congenital hydrocephalus in the dog - Poci Palumbo, Mariana Isa [UNESP]; Conti, Jorge Piovesan [UNESP]; Doiche, Danuta Pulz [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Gomes Lourenco, Maria Lucia [UNESP]; Araujo Machado, Luiz Henrique de [UNESP] (Univ Federal Santa Maria, 2011)
The complete absence of the eyeball is rare in dogs and cats, and hydrocephalus is commonly seen as a congenital disorder in toy or brachycephalic dogs before one year old. This paper describes for the first time in Brazil the occurrence of bilateral clinical anophthalmia associated to congenital hydrocephalus in a dog.
Keywords: neurology; dog; ophthalmology; congenital disorders